Comparison of Reability and Validity Chinese Four-Level and Three-District Triage Standard (CHT) and Australasian Triage Scale (ATS) - Achmad Fauzi; Muhammad Afdhol Zulfikri (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims : The increase in visits to the emergency room resulted in a buildup of patients and affected the services in the room.  The role of the emergency medical team in the initial assessment (triage) is very important to ensure that the right patient is in the right place at the right time and that nothing is missed. Nurses conduct studies and collect data accurately and consistently in 2 ways, namely reliability and validity. Methods : This type of research is quantitative with a comparative study design. The data collection instrument is primary data using a checklist observation sheet. The analysis used is univariate and bivariate. Results : Based on the results of the research conducted, it was shown that there were significant differences in the reliability and validity of the Chinese Four-Level and Three-District Triage Standard (CHT) and the Australasian Triage Scale (ATS) in emergency room patients with a p value = 0.000 (p <0.05). Conclusion : health workers, especially in the emergency room unit, will be able to perform triage quickly and accurately so as to reduce mortality.